Simulation of rail wheel axle bearing vibration due to local damages on outer races. (June 2019) - Liu, Hongbin; Wang, Ling; Li, Yunbin
This paper presents a dynamic model of bearings that simulates the vibration of rail wheel bearings due to local damages such as pits on the bearing outer race. The model, based on the multi-body simulation software RecurDyn, integrates the major parts of the functionalities according to the three-dimensional model and railway axle dynamic system. Three types of surface damages on the raceway of cylindrical roller bearings were designed and evaluated by the dynamic model developed in this study. The results show that the dynamic model can effectively simulate the influence of the damages on the bearing vibration under varied pit shape and size. Furthermore, the model can predict the level of bearing damage based on the peak value of bearing vibration in the frequency domain.